Cloud computing based on agent technology, super-recursive algorithms and DNA. (2018) - Burgin, Mark; Mikkilineni, Rao
Agents and agent systems are becoming more and more important in the development of a variety of fields such as ubiquitous computing, ambient intelligence, autonomous computing, data analytics, machine learning, intelligent systems and intelligent robotics. In this paper, we examine interactions of theoretical computer science with computer and network technologies analysing how agent technology emerged, matured and progressed in mathematical models of computation. We demonstrate how these models are used in the novel distributed intelligent managed element (DIME) network architecture (DNA), which extends the conventional computational model of information processing networks, allowing improvement of the efficiency and resiliency of computational processes. Two implementations of DNA described in the paper illustrate how the application of agent technology radically improves current cloud computing state of the art. First example demonstrates the live migration of a database from a laptop to a cloud without losing transactions and without using containers or moving virtual machine images. The second example exhibits the implementation of cloud agnostic computing over a network of public and private clouds where live computing process workflows are migrated from one cloud to another without losing transactions. Both these implementations demonstrate the power of scientific thought for dramatically extending the current state of the art of cloud and grid computing practice.